Diagnostic challenges in precocious puberty: A case of a 7-year-old girl - Asefeen, Jannatul; Hossain, Md Firoj; Ahammed, Afsar; Islam, Moinul; Sharifuzzaman, Mirza; Saifuddin, Mohammad; Prasad, Indrajit (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Immune-mediated destruction of two or more endocrine glands results in a cluster of deficits in multiple glands, known as autoimmune polyglandular syndrome. Autoimmune hypothyroidism is a common presentation of autoimmune polyglandular syndrome type II (APS–II). Long-standing, untreated hypothyroidism may cause isosexual precocious puberty, which is termed Van Wyk Grumbach syndrome. A 7-year-old girl was diagnosed with autoimmune hypothyroidism and type 1A diabetes mellitus and hence termed as autoimmune polyglandular syndrome type II. She had a history of menarche at the age of 2 years and 6 months and presented with bilateral ovarian cysts and delayed bone age. She was treated with thyroxine along with insulin. Thyroxine therapy stopped her menstruation with a reduction of ovarian cyst size. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2025;4(2): 90-95